2007
DOI: 10.2196/jmir.9.3.e27
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Emailed Messages on Return Use of a Nutrition Education Website and Subsequent Changes in Dietary Behavior

Abstract: Background At-risk populations can be reached with Web-based disease prevention and behavior change programs. However, such eHealth applications on the Internet need to generate return usage to be effective. Limited evidence is available on how continued usage can be encouraged.Objective This analysis tested whether routine email notification about a nutrition education website promoted more use of the website.Methods Adults from six rural counties in Colorado and New Mexico, United States (n = 755) participat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 33 publications
0
25
1
Order By: Relevance
“…Of those participants who opened at least one e-health message, 56% opened at least half of the messages sent. This current study appears to have had a higher participation percentage rate than reported by others (Woodall et al, 2007). Woodall and colleagues found that only 23% of study participants responded to at least one e-mail and that 51% of these participants responded to half of the e-mails, which is different than just opening e-mail messages.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…Of those participants who opened at least one e-health message, 56% opened at least half of the messages sent. This current study appears to have had a higher participation percentage rate than reported by others (Woodall et al, 2007). Woodall and colleagues found that only 23% of study participants responded to at least one e-mail and that 51% of these participants responded to half of the e-mails, which is different than just opening e-mail messages.…”
Section: Discussioncontrasting
confidence: 65%
“…Woodall and colleagues found that only 23% of study participants responded to at least one e-mail and that 51% of these participants responded to half of the e-mails, which is different than just opening e-mail messages. For the study by Woodall, participants logged-on to a nutrition website in order to determine participation (Woodall et al, 2007) which is more time consuming and requires several steps before participation is considered. The participation rate for this current study also compares favorably to the participation rate in typical worksite wellness programs (Franklin et al, 2006;Herman et al, 2006;Wilhide et al, 2008) all of which did not require extra steps to determine participation.…”
Section: Discussionmentioning
confidence: 99%
“…It was not known how frequently adults would use such a nutrition education website, and four visits was considered sufficient to receive the dietary information. To attract return visits, 13 updates to the 5 a Day, the Rio Grande Way website were published during the study period (Woodall et al, 2007). The majority of content remained unchanged, however, so that participants would receive essentially the same website intervention regardless of when they enrolled.…”
Section: A Day the Rio Grande Way Websitementioning
confidence: 99%
“…The Fruit and Vegetable All-day Screener has adequate validity ( r =0.68 in men and 0.49 in women) in white adults when compared to the By-Meal Screener (Thompson et al, 2000). This screener has been used widely in both AA and HL adult samples (Ahluwalia et al, 2007; Buller et al, 2008; Greene et al, 2008; Henry, Reimer, Smith, & Reicks, 2006; Resnicow et al, 2004; Resnicow et al, 2000; Thompson, et al, 2000; Thompson, et al, 2002; Woodall et al, 2007). The Fat Screener measures an individual’s usual dietary intake of percent calories from fat.…”
Section: Methodsmentioning
confidence: 99%